Development stakeholders and territorial identity in Portugal - Zoran Roca (European Regional Science Association (ERSA), 2001)
The need to reaffirm the diversity of places and regions in order to make them economically and culturally “more competitive” on the globalised market of goods and services has been widely accepted in regional and local development policies in Portugal, but much more so rhetorically than in operational terms. This largely reflects the fact that policies, as well as their instruments, do not rely on empirical evidence of the changing character of territorial identity. In particular, there are virtually no records regarding representations of territorial identity features and issues by local/regional development stakeholders, both individual and institutional ones. The problem is that appropriate conceptualisations and analytical tools for comprehensive identification and assessing of various dimensions local/regional identity have been lacking. Since it has not been clear what the identity of places and regions means in factual and verifiable terms to different development stakeholders, it is has not been possible to determine what aspects of the identity need to be strengthened, preserved, diversified, or made “more competitive” in regional and local development policy design and implementation. This paper brings forward a methodological framework for the study of the changing character of local identities and the role of local development stakeholders in this change. The region-specific evidence obtained from a nation-wide field survey of Portuguese local development agents' knowledge, attitudes and practice in relation to the territorial identity as a regional development issue is presented and discussed.
Keywords: 330